2015
DOI: 10.1109/jphot.2015.2445096
|View full text |Cite
|
Sign up to set email alerts
|

Quaternion Approach to the Measurement of the Local Birefringence Distribution in Optical Fibers

Abstract: A method to structure the Jones quaternion utilizing Pauli matrices is proposed, improving the quaternion theory of polarization optics. It is proved that the Stokes quaternion is the double product of the Jones quaternion and its Hermitian transpose and that the rotation axis of the output three-adjacent-point Stokes quaternions is a mapping from the rotation axis of the three-adjacent-reflection-point Stokes quaternions in the optical fiber and that the rotation angle among the output three adjacent points i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The experimental result showed that the average local birefringence of the fiber was 0.220 rad/m in the 17 km single-mode fiber under test, corresponding to a beat length of 28.5 meters. In 2015, Liu et al [16] proposed and implemented the three-point quaternion method to measure birefringence distribution for single-mode fiber. The experimental result showed that the average birefringence was 0.236 rad/m in the 1 km single-mode fiber under test, and the corresponding average beat length was 26.6 meters.…”
Section: Fine Spatial Resolution Birefringence Measurement With Pc-φ-mentioning
confidence: 99%
See 3 more Smart Citations
“…The experimental result showed that the average local birefringence of the fiber was 0.220 rad/m in the 17 km single-mode fiber under test, corresponding to a beat length of 28.5 meters. In 2015, Liu et al [16] proposed and implemented the three-point quaternion method to measure birefringence distribution for single-mode fiber. The experimental result showed that the average birefringence was 0.236 rad/m in the 1 km single-mode fiber under test, and the corresponding average beat length was 26.6 meters.…”
Section: Fine Spatial Resolution Birefringence Measurement With Pc-φ-mentioning
confidence: 99%
“…However, such methods have strict requirements for the polarization alignment-the angles between the polarization of the input linearly polarized light and the principal axis of the Wollaston prism should be precisely adjusted to 45°. The scattering-based birefringence measurement scheme includes two typical types, which are Brillouin-scattering (BS) based [11,12] birefringence measurement systems and Rayleighscattering (RS) based [13][14][15][16][17] birefringence measurement systems. As for the BS based systems, Lu et al [12] proposed a system with beat period detection of homodyne Brillouin optical time-domain reflectometry (BOTDR), but this system's signal-to-noise ratio (SNR) highly depends on the input pulses' state of polarization (SOP) and it takes 80 seconds to complete once measurement.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…. From the formula (10) it immediately follows that a very similar transformation (rotation) applies to the Stokes quaternion (see also Liu et al [8]):…”
Section: B Transformaton Of a Stokes Quaternionmentioning
confidence: 99%